Structural Valve Deterioration After Aortic Valve Replacement with Medtronic Freestyle Stentless Porcine Aortic Root Bioprostheses. Issue 1 (22nd October 2013) - Nishida, Hidefumi; Komiya, Tatsuhiko; Sakaguchi, Genichi; Shimamoto, Takeshi
Abstract The Medtronic freestyle aortic root bioprosthesis (Medtronic, Inc., Minneapolis, MN, USA) is a stentless valve with an effective orifice area that is larger than that observed on other bioprostheses. However, there have been sporadic reports of structural valve deterioration (SVD), such as aortic root wall rupture, leaflet tearing, and pseudoaneurysm formation. We report five cases of SVD of freestyle aortic root bioprostheses. doi: 10.1111/jocs.12235 (J Card Surg 2014;29:22‐25)